Arsitektur Jaringan Menggunakan Topologi Tree - Nur Fajri Fa’iz; Danna Rayana Irfawan; Aulivia Widya Putri; Syarif Hidayatullah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Architecture using tree topology has become a popular approach in managing computer networks. Tree topology combines elements of star and bus topologies, resulting in an efficient and scalable network for a variety of purposes. This paper discusses the basic concepts of architecture using tree topology, including hierarchical structures and design advantages. First, the tree topology consists of a parent node (root node) which leads to a number of branch nodes (branch nodes). Each branch node can then connect to other nodes, forming a multilevel hierarchy. In computer networks, this topology is often used to connect a number of LANs (Local Area Networks) into a larger network. The main advantages of tree topology are scalability and management efficiency. The network can be expanded by adding new branch nodes without affecting the rest of the network. Additionally, network monitoring and maintenance becomes more organized due to a clear hierarchical structure. However, tree topology also has disadvantages. If the parent node fails, then all parts of the network connected to that node can be affected. Additionally, complex implementations may require more sophisticated hardware and software. In the modern computing era, tree topologies are used in a variety of contexts, ranging from corporate network infrastructure to online content distribution. Its ability to provide an organized and extensible structure makes it an attractive choice in designing efficient and reliable network architectures.